2020
DOI: 10.1109/tbme.2020.2973934
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Engine: A Reprogrammable Low Power Platform for Closed-Loop Optogenetics

Abstract: Brain-machine Interfaces (BMI) hold great potential for treating neurological disorders such as epilepsy. Technological progress is allowing for a shift from open-loop, pacemaker-class, intervention towards fully closed-loop neural control systems. Low power programmable processing systems are therefore required which can operate within the thermal window of 2O C for medical implants and maintain long battery life. In this work, we have developed a low power neural engine with an optimized set of algorithms wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Table 3 compares features of the different components of this device with existing clOBS devices. These other clOBS devices were reported by Turcotte et al [20], Liu et al [45], Ramezani et al [46,47] and Mendrela et al [48]. While most of these devices are tetherless, the current work is the first device to use on-device processing of neural signals using an AI-based algorithm, along with miniaturization and tetherless operation.…”
Section: Discussionmentioning
confidence: 66%
“…Table 3 compares features of the different components of this device with existing clOBS devices. These other clOBS devices were reported by Turcotte et al [20], Liu et al [45], Ramezani et al [46,47] and Mendrela et al [48]. While most of these devices are tetherless, the current work is the first device to use on-device processing of neural signals using an AI-based algorithm, along with miniaturization and tetherless operation.…”
Section: Discussionmentioning
confidence: 66%
“…Using gene therapy to target specific types of neurons to be sensitive to particular optical wavelengths has significant potential in neuroprosthetics as a whole. We have previously explored optogenetic approaches to retinal prosthesis [32,33] and Luo et al [34] recently demonstrated how are technology could be used for closed-loop control methodologies. A similar approach could potentially be used to improve visual prosthetics.…”
Section: Introductionmentioning
confidence: 99%